Imprimer les émotions : stratégies du narrateur dans la quatrième Histoire tragique de Bénigne Poissenot - Marczuk, Barbara (Studia Romanica Posnaniensia, 2018)
Bénigne Poissenot was the first author to introduce the theory of tragic tales reception, which was a vastly popular genre by the end of 16th and the beginning of 17th century in France. In the prologue of Nouvelles Histories Tragiques (1586) he emphasizes that the reason of his tales is to move the readers deeply and make them choose to go through a moral transformation and to live virtuous lives. This article’s objective is to investigate what methods and strategies the narrator uses to influence a reader’s emotions and to what extent those emotions help (or not) deliver the moral message, which can be found in his first-person declarations (the introduction and the conclusion of the tale). It is done by examining the fourth novel.